Amplification of gibberellins response in tomato modulates calcium metabolism and blossom end rot occurrence - Gaion, Lucas Aparecido [UNESP]; Muniz Junior, Jean Carlos [UNESP]; Barreto, Rafael Ferreira [UNESP]; D'Amico-Damiao, Victor [UNESP]; Prado, Renato de Mello [UNESP]; Carvalho, Rogerio Falleiros [UNESP] (Elsevier B.V., 2019)
Blossom end rot is one of the main physiological disorders of the tomato crop. Usually, the blossom end rot (BER) occurrence is associated with fruit calcium (Ca2+) deficiency; however, increasing evidence of Ca2+ disorders and hormonal regulation has emerged. Therefore, the present work was undertaken to investigate the role of gibberellin (GA) signaling on the control of tomato plant responses to Ca2+ deficiency. In this study, we used the tomato mutant procera (pro), which has a constitutive response to GA, and its isogenic line cv. Micro-Tom (MT) grown in a hydroponic system with or without Ca2+. Subsequently, the analysis of the growth of the shoot and the root system was performed, and the contents of photosynthetic pigments and oxidative stress were also analyzed. Furthermore, the fruit production, BER incidence, accumulation and metabolism of Ca2+ were also analyzed. The deficiency of Ca2+ reduced both shoot and root growth in both genotypes. Likewise, photosynthetic pigment degradation and oxidative stress were induced by Ca2+ deficiency. However, only pro plants exhibited the inhibition of fruit dry mass, as well as a higher incidence of BER, when exposed to Ca2+ deficiency compared to MT plants. In accordance with the greater pro susceptibility to Ca2+ deficiency, the efficiency of the transport, use and accumulation of Ca2+ in fruits was lower in pro when compared to the MT. Thus, we conclude that the higher sensitivity to GA in pro plants impairs Ca2+ metabolism and favors the occurrence of BER in tomato fruits, opening new approaches for the GA signaling on BER response.
Keywords: Calcium deficiency; Plant hormones; Gibberellin mutant; Plant nutrition; Physiological disorders